ARA-PEPs: a repository of putative sORF-encoded peptides in Arabidopsis thaliana. Issue 1 (December 2017) - Hazarika, Rashmi; De Coninck, Barbara; Yamamoto, Lidia; Martin, Laura; Cammue, Bruno; van Noort, Vera
Abstract Background Many eukaryotic RNAs have been considered non-coding as they only contain short open reading frames (sORFs). However, there is increasing evidence for the translation of these sORFs into bioactive peptides with potent signaling, antimicrobial, developmental, antioxidant roles etc. Yet only a few peptides encoded by sORFs are annotated in the model organismArabidopsis thaliana . Results To aid the functional annotation of these peptides, we have developed ARA-PEPs (available athttp://www.biw.kuleuven.be/CSB/ARA-PEPs ), a repository of putative peptides encoded by sORFs in theA. thaliana genome starting from in-house Tiling arrays, RNA-seq data and other publicly available datasets. ARA-PEPs currently lists 13, 748 sORF-encoded peptides with transcriptional evidence. In addition to existing data, we have identified 100 novel transcriptionally active regions (TARs) that might encode 341 novel stress-induced peptides (SIPs). To aid in identification of bioactivity, we add functional annotation and sequence conservation to predicted peptides. Conclusion To our knowledge, this is the largest repository of plant peptides encoded by sORFs with transcript evidence, publicly available and this resource will help scientists to effortlessly navigate the list of experimentally studied peptides, the experimental and computational evidence supporting the activity of these peptides and gain new perspectives for peptide discovery.